Bus Roll-Over Simulation Using Computer Techniques on the Basis of Measurement Results - Voith, A. (Engineering Transactions, 1981)
The purpose of this paper was to present a method whereby test results concerning the plastic the formation of a sophisticated structure were built into a simulation program which describes the whole process. The reason why test results were used was that at the present time we do not have a suitable and reliable method for the theoretical description of the plastic deformation of the investigated, statically indeterminate structure. The results calculated in accordance with the Hungarian proposal and those of crash tests were compared and the comparison proved the applicability of this method. Comparing it to the roll-over test it has a significant advantage: the application of computer simulation on the basis of laboratory tests of structural parts put together makes it possible to check the accomplishment of passive safety requirements in the early stage of design, before producing the prototype. The development and application of the method is not completed. On the one hand, improvement of the model is possible and on the other hand there is a possibility to take into consideration other roll-over test conditions by applying the method and modifying the program.